Hubungan Kemampuan Pemecahan Masalah Matematika dengan Self Efficacy Siswa Kelas VIII di SMP Negeri 1 Kabila - Yusuf, Robiatul Dalwia; Abdullah, Abdul Wahab; Pauweni, Khardiyawan A.Y (Mandalika Mathematics and Educations Journal, 2025)
This study aims to identify whether there is a relationship between mathematical problem solving ability and self efficacy of VIII grade students at SMP Negeri 1 Kabila. The subjects in this study were students of class VII-D as many as 30 students. The method used in this research is a type of correlation research with a survey method using a quantitative approach and the correlation test used is the Pearson correlation test.. The technique used to analyze the data is correlation to determine the relationship between mathematical problem solving ability and self efficacy. The instruments in this study were mathematical problem solving ability test questions and non-tests in the form of self efficacy questionnaires. The results showed that there was a positive correlation between self efficacy and problem solving ability, where self efficacy contributed to problem solving ability by 45.36%.